Study on proton-conducting solid oxide fuel cells with a conventional nickel cermet anode operating on dimethyl ether - Liu, Y.; Guo, Y.; Wang, W.; Su, C.; Ran, R.; Wang, H.; Shao, Zongping (2011)
This study investigates dimethyl ether (DME) as a potential fuel for proton-conducting SOFCs with a conventional nickel cermet anode and a BaZr 0.4Ce0.4Y0.2O3-d (BZCY4) electrolyte. A catalytic test demonstrates that the sintered Ni + BZCY4 anode has an acceptable catalytic activity for the decomposition and steam reforming of DME with CO, CH4 and CO2 as the only gaseous carbon-containing products. An O2-TPO analysis demonstrates the presence of a large amount of coke formation over the anode catalyst when operating on pure DME, which is effectively suppressed by introducing steam into the fuel gas. The selectivity towards CH4 is also obviously reduced. Peak power densities of 252, 280 and 374 mW cm-2 are achieved for the cells operating on pure DME, a DME + H2O gas mixture (1:3) and hydrogen at 700 °C, respectively. After the test, the cell operating on pure DME is seriously cracked whereas the cell operating on DME + H2O maintains its original integrity. A lower power output is obtained for the cell operating on DME + H2O than on H2 at low temperature, which is mainly due to the increased electrode polarization resistance. The selection of a better proton-conducting phase in the anode is critical to further increase the cell power output. © 2011 Elsevier B.V.